Researching street-level bureaucracy bringing out the interpretive dimensions - Rowe, Michael 1967- (Routledge, 2025)
"Police officers, social workers, teachers, and many other street-level bureaucrats exercise discretion in dealing with clients. In so doing, they make policy as it is experienced at the frontline. Instead of puzzling at repeated public policy implementation failures and wondering why street-level bureaucrats (SLBs) don't behave the way policymakers expect, we need to understand the world as seen from the ground. This short and practical text explores the value of interpretive analysis for researching street-level bureaucracy.